A history of Christian-Muslim relations - Goddard, Hugh (New Edinburgh Islamic surveys., 2020)
"Christians and Muslims comprise the world's two largest religious communities. This book looks at the history of their relationship--part peaceful co-existence and part violent confrontation--from their first encounters in the medieval period up to the present."--